POTENSI AVIFAUNA UNTUK PENGEMBANGAN EKOWISATA BIRDWACTHING DI DESA EKOWISATA BAHOI - Meike D. Lakiu; Martina A. Langi; Hard N. Pollo (COCOS, 2016)
ABSTRACTAVIFAUNA POTENCY FOR DEVELOPING BIRDWACTHING ECOTOURISM IN THE VILLAGE OF ECOTOURISM BAHOIThe research aimed to study diversity, distribution, and avifauna potency for birdwacthing ecotourism in the mangrove vegetation of Bahoi village, west of Likupang, North Minahasa. The research was conducted from June to September 2015. The purposive method was used to collect data. Observations were made at 36 points determined based on bird preferences. From that observations it was found 47 bird spesies, belonging to 25 families. Among all the species, 65.9% is categorized as resident, 23.4% as endemik of Sulawesi, and 10.6% as migratory. Based on the government regulation (PP No. 7, 1999), there are 12 protected birds spesies within the resident and Sulawesian endemic species. The value of diversity in this mangrove was 3.24 or higher than Shannon-Wiener criteria. Index of eveness was 0.84 or higher than Magguran criteria. Based on all the values obtained, two birdwatching lines for ecotourism were proposed.Keywords: avifauna, bird diversity, ecotourism, birdwacthing.